ANALISIS DISPARITAS SEKTORAL UNTUK PENGENTASAN KEMISKINAN KABUPATEN BANTUL SAAT COVID-19 - wulandari, meisyaroh catur; Wicaksono, Rayhan Arya; Mukharohmah, Maulia Siti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2023)
Community disparities are related to the existence of poverty in an area. So that a region needs to know how big the sectoral disparity is and know the potential of a region. During the Covid19 pandemic, Bantul Regency, which counted from 2020-2022, occupies the 2nd position in the Province of the Special Region of Yogyakarta with an average poverty rate of 138.59 thousand residents. This study aims to determine the level of sectoral disparities and map regional potential through the economic base sector of Bantul Regency during the Covid-19 pandemic in 2020-2022. The analytical tools used include theil entropy index analysis and location quotient (LQ) analysis. Sectoral disparity is below 0.5, meaning that economic disparity is still low, and it is known that the economic base sector includes agriculture, forestry and fisheries; processing industry sector; electricity and gas procurement sector; wholesale and retail trade sector as well as car and motorcycle repair; transportation and warehousing sector; the sector of providing accommodation and food and drink.